PENINGKATAN KOMPETENSI PETERNAK DOMBA MELALUI PROGRAM PELATIHAN PENGOLAHAN PAKAN FERMENTASI (SILASE - Faris Rahmat Hidayat; Sri Nurhayati (Comm-Edu (Community Education Journal), 2023)
Abstract The background of the research is the results of the Inter-Census Agricultural Survey (2018) that the number of livestock households in Indonesia reaches 13.56 million households. The success of livestock development as a sub-sector that contributes to the improvement of the national economy will be largely determined by human resources, namely breeders as the main actors of livestock activities themselves. Increased competence has a very important role in improving the ability of farmers, especially in this study are sheep breeders. The purpose of this study was to determine the competency improvement of sheep breeders through a fermented feed processing training program (silage). The research method that the researcher used was descriptive qualitative research with data collection methods through interviews and observations. The sample of this study were five farmers who participated in the training, one training facilitator, and one community leader. The research site is in Cipada Village, Cikalong Wetan District, West Bandung Regency.The results of this study are to provide a positive impact and benefit in the long term for farmers, namely increasing the knowledge, skills and independence of farmers in animal feed management and for the sustainability of sheep breeders so that farmers are able to survive in the times. The community becomes empowered by participating in Fermented animal feed processing training. Keywords: Sheep Breeder Competence, fermented animal feed processing Training. Abstrak Latar belakang penelitian ini adalah berdasarkan hasil Survei Pertanian Antar Sensus (2018) Indonesia memiliki 13,56 juta peternakan rumah tangga. Keberhasilan pembangunan peternakan sebagi subsector yang berkontribusi dalam peningkatan perekonomian nasional akan sangat ditentukan oleh sumber daya manusia yaitu peternak sebagai pelaku utama dari kegiatan peternakan itu sendiri. Peningkatan kompetensi mempunyai peranan yang sangat penting dalam meningkatkan kemampuan peternak, khususnya dalam penelitian ini ialah peternak domba. Tujuan dari penelitian ini adalah untuk mengetahui peningkatan kompetensi peternak domba melalui program pelatihan pengolahan pakan fermentasi (silase). Metode penelitian yang digunakan oleh peneliti adalah penelitian kualitatif deskriptif dengan metode pengumpulan data melalui wawancara dan observasi. Sampel penelitian ini adalah lima orang peternak peserta pelatihan, satu orang fasilitator pelatihan, dan satu orang dari tokoh masyarakat. Tempat penelitian di Desa Cipada, Kecamatan Cikalong Wetan Kabupaten Bandung Barat.Hasil dari penelitian ini adalah memberikan dampak positif dan kebermanfaatan dalam jangka panjang bagi peternak yaitu peningkatkan pengetahuan, keterampilan dan kemandirian peternak dalam pengelolaan pakan ternak dan bagi keberlanjutan peternak domba sehingga peternak mampu bertahan dalam perkembangan zaman. Masyarakat menjadi berdaya dengan mengikutii pelatihan pengolahan pakan ternak.Kata Kunci: Kompetensi, Peternak domba, pelatihan pengolahan pakan